Evaluating Good Governance in Preserved Forests: a Comparison Between Community-based and State-based Forest Management in South Sumatera - Pamungkas, Wahyu; Muluk, M. R. Khairul; Rochmah, Siti; Jones, T. E. (Jurnal Ilmiah Administrasi Publik, 2018)
In Indonesia, the existence of preserved forest is threatened by the high rate of deforestation associated with poor quality of governance. This study aims to evaluate the applying of good governance principles in preserved forest at South Sumatera and its effect on deforestation. This study is a qualitative research. Good governance principles refer to Lockwood (2009) which consists of seven principles. This study reveals that SBFM is better than CBFM in applying good governance principles by earning the higher appraisal results compared to CBFM for all principles. Furthermore, applying good governance principles did not lead directly to lower deforestation rate.